SIFAT-SIFAT MEKANIS ASPAL YANG DITAMBAHKAN SERBUK ARANG TEMPURUNG KELAPA - Mashuri, Mashuri; Maricar, M. Husni (MEKTEK, 2006)
The objective of this research is to know mechanical properties of bitumen mixtures coconut charcoal powder. This research was done in Highway and transportation laboratory of Civil Department, Tadulako University. Percentage of coconut charcoal powder content based on weight of bitumen. The percentage of coconut charcoal powder in bitumen are 2%, 4%, 6% and 8% respectively and comparison with properties of bitumen without additive material. The properties of bitumen include the following: the penetration value of bitumen, the Ductility value, the softening point value, density of bitumen value, loss on heating of bitumen, flash and fire point of bitumen values.The result of this research indicates that the coconut charcoal powder in bitumen between 2% to 8% still enough for spesification except on ductility properties of bitumen values. This implies that, increment the coconut charcoal in bitumen potential influence on asphalt pavement include stiffness and brittle of mixtures.